2009
DOI: 10.1007/s11869-009-0039-x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of individual airborne particles in Taiyuan City, China

Abstract: Taiyuan, the capital of Shanxi province, China, is one of the most polluted cities in the world. To characterize the ambient particulate pollution, samples of particulates with aerodynamic diameter less than 10 µm (PM10) were collected during a 6-day campaign. Individual particles were analyzed by Scanning Electron Microscope with Energy-Dispersive Spectrometer (SEM-EDS) to determine their chemical composition. Meanwhile, photomicrographs were obtained from SEM to aid in particles’ source identification. The l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 7 publications
0
20
0
Order By: Relevance
“…4c). Chemical compositions of these particles were predominately aluminosilicates, which is similar to the soil particles (Xie et al 2005(Xie et al , 2009). However, the soil particles usually have pronounced irregular shapes; the fly ash particles are, in most cases, nearly spherical.…”
Section: Fly Ashmentioning
confidence: 65%
See 1 more Smart Citation
“…4c). Chemical compositions of these particles were predominately aluminosilicates, which is similar to the soil particles (Xie et al 2005(Xie et al , 2009). However, the soil particles usually have pronounced irregular shapes; the fly ash particles are, in most cases, nearly spherical.…”
Section: Fly Ashmentioning
confidence: 65%
“…Iron can originate from both natural and anthropogenic sources, e.g., from soil, mining, and ferrous metallurgic industry. Besides, contribution from coal combustion is also possible, and particles can be formed by oxidation of pyrite (FeS 2 ) in coal (Xie et al 2009). Emitted by hightemperature furnaces, these particles are usually spherical (Cong et al 2010).…”
Section: Other Particlesmentioning
confidence: 99%
“…For morphology study, PTFE filter is causing the positive artifacts and uncertainties because of its fiber structure. But, still some studies have been reported SEM-EDS on PTFE (Wheeler et al 2000;Xie et al 2009;Slezakova et al 2008;Pipal et al 2011). Moreover, present study was performed during the monsoon season (June-September) when the relative humidity is very high (80-90 %).…”
Section: Sample Collectionmentioning
confidence: 89%
“…Taiyuan, the capital of Shanxi Province, is one of the most heavily polluted cities in the world, with large coal consumption for energy production and many industrial activities including electricity, coke, steel and chemical products, and unfavorable dispersion condition of hills on three sides and a marked continental monsoonal climate [12,13]. Combined with strong administrative action and improvement of the pollution control technologies, the SO2 and PM10 concentrations decreased steadily, but still exceed the second threshold of China National Ambient Air quality Standard (NAAQS) [14].…”
Section: Introductionmentioning
confidence: 99%